Eucalyptus dunnii Maiden plant regeneration via shoot organogenesis on a new basal medium based on the mineral composition of young stump shoots - Oberschelp, Gustavo Pedro Javier (2015)
Eucalyptus dunnii is an excellent alternative for afforestation and reforestation in frost-prone areas; however, it has limitations in the availability of propagation material. Given the great potential of tissue culture techniques for plant propagation and plant genetic transformation, the competence for in vitro organogenesis from E. dunnii cotyledons and hypocotyls was assessed. Several combinations of 6-benzylaminopurine (BAP) plus α-naphthalene acetic acid (NAA) or indole-3-acetic acid (IAA) were added (0, 0.1, 0.5, and 1 mg l−1) to a specifically developed basal medium. Moreover, the effect of the hypocotyl segments position (distal and proximal) on bud and callus regeneration was studied. Finally, microcuttings obtained from in vitro multiplication of the regenerated buds were treated with different dosages of indole-3-butyric acid (IBA) or NAA (powder based) and rooted under ex vitro conditions. Bud regeneration was observed only in hypocotyl segments, where dosages of 0.5 mg l−1 BAP plus 0.5 mg l−1 NAA or 0.5 mg l−1 IAA and distal segments resulted in higher bud regeneration rates. Histological analyses suggest that callus regeneration areas in hypocotyl explants recreate an appropriate niche for the development of pluripotent cells that give rise to buds and shoots. Either IBA or NAA treatments failed to significantly improved the ex vitro rooting of E. dunnii microcuttings, whereas >50% microcuttings rooted without application of growth regulators.